Linoleic acid addition prevents Staphylococcus aureus biofilm formation on PMMA bone cement - Linglu Hong; Karin Hjort; Dan I. Andersson; Cecilia Persson (Biofilm)
Acrylic bone cement is widely used in vertebroplasty to treat osteoporosis-induced vertebral compression fractures. However, infection after vertebroplasty is problematic and previous work has suggested loading the bone cement with an antibiotic for prophylaxis. Linoleic acid (LA) has been investigated as a promising additive to improve the mechanical properties of bone cement for vertebroplasty, but LA could potentially also have an antibacterial effect. In this study, we evaluated the antibacterial properties of LA-loaded bone cement by comparing its antibiofilm properties with that of original bone cement through quantification of bacterial growth using viable cell count and scanning electron microscopy. The released monomer (MMA) concentration and the monomer minimum inhibitory concentration were determined to clarify the monomer's potential role in inhibiting bacterial growth. The LA release profile was measured, and a checkerboard assay was done to determine any synergistic effects of LA and the commonly used antibiotic gentamicin. Results show that LA-loaded bone cement could significantly inhibit Staphylococcus aureus biofilm formation, including gentamicin-resistant strains, but with limited effect on Escherichia coli. Furthermore, the released MMA did not have a significant influence on bacterial growth. The checkerboard assay results show that the LA and gentamicin combination could broaden the antibacterial spectrum and increase gentamicin efficacy. In conclusion, LA merits further investigation as an antibacterial agent in bone cement, alone or in combination with antibiotics.